Charge migration of ferrocene-labeled peptide self-assembled monolayers at various interfaces: The roles of peptide composition. (20th June 2023) - Zhu, Xixia; Xu, Zhongchen; Li, Xiaobing; Guo, Cunlan
Abstract: Understanding charge migration across peptide chain of proteins is important for both biology and biomolecular electronics. Despite experimental and theoretical researches showing that the charge migration in wet electrochemistry and on solid state are interrelated, there are still limited insights about this interrelation. Here, taken ferrocene-labeled peptide self-assembled monolayers on the Au substrate as a model, the relation between the charge migration on solid state (charge transport, CTp) and in wet electrochemistry (charge transfer, CT) was investigated. By characterizing the current density from solid state molecular junctions and the electron transfer rate (kET ) from electrochemical measurement in solution, we found that the ability of peptides to transmit charge was more sensitive to peptide's length on solid state than that in wet electrochemistry, comparing to the reported alkane and peptide nucleic acid oligomers. In addition, changing peptide compositions, such as doping phenylalanine (F) or aspartic acid (D) into the initial glycine (G) peptide backbone, made a different consequence for charge migration: the kET in wet electrochemistry was F > G ≈ D, while the CTp rate on solid state was G ≈ F > D . Our findings provide further insights into the comprehension of relations between charge migration and peptide structures. Graphical abtract: Image, graphical abstract